Answer:
Explanation:
The two descriptions can be written as two equations. We can let "m" and "c" represent the amounts that Mia and Charlie have to begin with. Then ...
m -9 = c+9 . . . . . equal amounts if Mia gives Charlie $9
m +9 = 2(c -9) . . Mia has double if Charlies gives Mia $9
Subtracting the first equation from the second gives ...
(m +9) -(m -9) = (2(c -9)) -(c +9)
18 = c -27 . . . simplify
45 = c . . . . . . add 27
Substituting into the first equation, we have ...
m -9 = 45 +9
m = 63 . . . . . . . add 9 and simplify
Charlie and Mia started with $45 and $63, respectively.